The Boasian Text Tradition and the History of Anthropology - Darnell, Regna (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1992)
The North American anthropological tradition, as a whole, contrasts sharply with the anthropologies which grew up elsewhere in the Western world, and forms a distinct part of contemporary anthropology on an international scale, a part which is accessible to us through disciplinary history. In this article I first argue for an historical approach as integral to mature disciplinary theory, and will then examine a specific moment in the history of North American anthropology as a microcosm of the differences between the British and North American traditions.